Understanding the Taxpaying Behaviour of the Informal Sector of Ghana Towards Improved Public Revenue Mobilization - Otieku, J.K. (My University, 2013)
This paper examines the taxpaying behaviour among players in the informal sector (INFS) that accounts for their relatively low contribution to tax revenue in Ghana. The main reasons established for the hard-to-tax nature of the INFS include: predominance of cash transactions, high level of poor accounting practices and illiteracy rates among operators in the sector. It is therefore not surprising that the explanatory variables for the high tax non-compliance behaviour in the INFS include: unknowing, procedural, habitual, brokered/advised, protest/symbolic and asocial. Accounting non-compliance dominates non-compliance behaviour of the INFS. The poor response of the INFS to the tax amnesty policy initiated by the Government of Ghana in 2006 year of assessment lends credence to the low level of tax consciousness and awareness in the INFS in Ghana. Recommendations in respect of capacity building programmes in record keeping; intensive and sustained tax education programmes; simplification of tax filing procedures; etc are suggested to improve the contribution of the INFS to tax revenue in Ghana.